Manifestation of Hadiths in Environmental Preservation - Nuraini, Nuraini (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2023)
Humans and the environment are inseparable partners. The environment is our home, where we live and interact with everything around us, both living and non-living. Allah SWT has created this environment to meet our needs, as we depend on it for our survival. This shows how crucial it is for us to treat our environment wisely, ensuring it can continue supporting us. However, not everyone treats the environment wisely. Sometimes people prioritize their own interests without considering the long-term health of nature. This can lead to resources running out or becoming damaged. This article explores how the teachings of Prophet Muhammad SAW guide us in preserving the environment, both through what he said and what he did. Prophet Muhammad SAW’s guidance encourages us to act responsibly when using the environment. These teachings also highlight that we are responsible for taking care of the environment, as Allah SWT has chosen us to look after it. Allah SWT knows that humans can be greedy and harm nature. So, Allah SWT has rewards and consequences based on how we treat the environment. When we follow Islamic teachings, we are rewarded, and when we disregard them, there are consequences. Following these teachings means thinking about the environment’s long-term well-being. It means taking positive care of nature so that all of Allah SWT’s creations—living things and the environment—can thrive. Ultimately, this approach benefits us, leading to a complete, beautiful, peaceful, healthy, and refreshing environment